Post-irradiation sarcoma after definitive radiation therapy for nasopharyngeal carcinoma. (January 2023) - Chen, Wan-Yu; Lu, Szu-Huai; Wang, Yu-Ming; Wang, Chun-Wei; Fang, Ku-Hao; Lai, Shih-Fan; Liang, Hsiang-Kuang; Huang, Bing-Shen
Highlights: Postirradiation sarcoma (PIS) is a rare radiation-induced malignancy after nasopharyngeal carcinoma (NPC) treatment. DVH analysis demonstrated that PIS occurred mainly within high dose (>55Gy) region. Higher radiation energy and modern technology were associated with shortened PIS latency time. After PIS development, surgery, compared with radiation or systemic therapy, was associated with better survival. Abstract: Background and purpose: Postirradiation sarcoma (PIS) is a rare radiation-induced malignancy after nasopharyngeal carcinoma (NPC) treatment. Materials and methods: We retrospectively screened 9, 185 NPC patients between 2000 and 2020 and identified 41 patients with PIS according to the modified Cahan's criteria: (1) the PIS must have arisen within a previous radiation field; (2) a latent period must have existed; (3) histologically proved sarcoma; (4) the tissue in which the PIS arose must have been healthy prior to the radiation. The initial radiation therapy techniques used were 2D (25; 61.0%), 3D (7; 17.1%), and IMRT (9; 22%). Results: The time (year) from radiotherapy (RT) to PIS was longer when using 2D or 3D irradiation techniques (median, 14.2; range, 3.4–28.1; Q1-Q3, 8.6–19.7) than when using IMRT (median, 6.6; range, 3.8–15.7; Q1-Q3, 4.5–11.7; P =.026). The time (year) from RT to PIS diagnosis was significantly longer when using lower radiation energy from cobalt-60 (median, 15.8; range, 10.4–28.4; Q1-Q3, 12.5–23.8) than when using a higher radiation energy of 6 or 10 MV (median, 10.2; range, 3.4–23.3; Q1-Q3, 6.5–16.1; P =.006). The 2-year overall survival rates for patients who underwent surgery, radical radiotherapy, systemic therapy alone and no treatment were 60.7 %, 42.9 %, 0 % and 0 %, respectively (P =.000). Of the 3 retrievable initial RT dosimetry plans for NPC, the D95 values (dose that covers 95 % of the PIS volume) for PIS were 6267, 6344 and 5820 cGy, respectively. Conclusion: High radiation energy and modern techniques may shorten NPC PIS latency. Surgery may be associated with improved survival if feasible.